A Metafrontier Production Function for Estimation of Technical Efficiencies of Wheat Farmers under Different Technologies - Ali, K.M Earfan; Samad, Q.A (Journal of Asian Scientific Research, 2013)
The paper presents a metafrontier production function model for farm’s different groups having different technologies. The metafrontier model enables the computation of comparable technical efficiencies for farms operating under different technologies. The model also enables the technology gaps to be estimated for wheat farms under different technologies relative to the potential technology available to the farms as a whole. The metafrontier model is applied in the analysis of panel data on wheat farms in five different regions of Bangladesh, assuming that the regional stochastic frontier production function models have technical inefficiency effects with the time-varying structure proposed by Battese and Coelli (1992).